A Unique Case of Midvariant Reverse Takotsubo Cardiomyopathy - Carmel Moazez; Vicken Zeitjian; Azar Mehdizadeh (Case Reports in Cardiology)
Takotsubo cardiomyopathy, also known as stress cardiomyopathy, is known to have 4 variants: apical, midventricular, basal, and focal. Here, we report the 2nd case of reverse midvariant (midventricular) stress cardiomyopathy and the 1st case of reverse midvariant takotsubo cardiomyopathy with apical thrombus.